2017
DOI: 10.1016/j.csr.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Bottom trawl impacts on Mediterranean demersal fish diversity: Not so obvious or are we too late?

Abstract: Measures of biodiversity change may be useful as indicators if they are responsive to manageable drivers of biodiversity loss. However, there are many candidate indicators that are considered to be robust to survey artifacts and sensitive to manageable impacts. Using extensive survey data on demersal fish assemblages around the Balearic Islands (western Mediterranean) we analyze relationships among 'traditional', taxonomic and functional diversity indices, to identify a minimum set of indices that provide a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 77 publications
4
23
0
Order By: Relevance
“…The increasing trend in N 90 with decreasing fishing effort reinforces the previous results that confirm the usefulness of this index for detecting the effects of fishing on demersal fish diversity. The increase of evenness with increasing fishing effort has been suggested by some authors (Murawski 2000, Zhou et al 2010 due to the reduction of dominant species by fishing (Cury et al 2000, Rice 2000 and has been confirmed by the study of the effects of fishing on evenness indices (D'Onghia et al 2003, Farriols et al 2017. However, the expected increase in S and decrease in J' with decreasing fishing effort are not always observed in our results.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The increasing trend in N 90 with decreasing fishing effort reinforces the previous results that confirm the usefulness of this index for detecting the effects of fishing on demersal fish diversity. The increase of evenness with increasing fishing effort has been suggested by some authors (Murawski 2000, Zhou et al 2010 due to the reduction of dominant species by fishing (Cury et al 2000, Rice 2000 and has been confirmed by the study of the effects of fishing on evenness indices (D'Onghia et al 2003, Farriols et al 2017. However, the expected increase in S and decrease in J' with decreasing fishing effort are not always observed in our results.…”
Section: Discussionsupporting
confidence: 81%
“…The spatial distribution of the bottom trawl fishing effort by GSA shows that the number of vessels per km 2 is low on the continental shelf of the Balearic Islands, Sardinia and the Aegean Sea (Colloca et al 2017). The coincidence of areas with a low fishing effort with areas with a high diversity is in accordance with previous works, in which higher values of N 90 and S and lower values of J' were associated with areas with a low fishing effort (Farriols et al 2017). The lower fishing effort exerted by the relatively smaller bottom trawl fleets in these areas could have preserved, at least to some extent, their fish diversity along with a better conservation of their sensitive and essential habitats, such as maerl and Peyssonnelia beds.…”
Section: Stratumsupporting
confidence: 89%
See 3 more Smart Citations